MiR-190b, the highest up-regulated miRNA in ERα-positive compared to ERα-negative breast tumors, a new biomarker in breast cancers? - Cizeron-Clairac, Geraldine (BMC Cancer, 2015)
BACKGROUND: MicroRNAs (miRNAs) show differential expression across breast cancer subtypes and have both oncogenic and tumor-suppressive roles. Numerous microarray studies reported different expression patterns of miRNAs in breast cancers and found clinical interest for several miRNAs but often with contradictory results. Aim of this study is to identify miRNAs that are differentially expressed in estrogen receptor positive (ER(+)) and negative (ER(−)) breast primary tumors to better understand the molecular basis for the phenotypic differences between these two sub-types of carcinomas and to find potential clinically relevant miRNAs. METHODS: We used the robust and reproductive tool of quantitative RT-PCR in a large cohort of well-annotated 153 breast cancers with long-term follow-up to identify miRNAs specifically differentially expressed between ER(+) and ER(−) breast cancers. Cytotoxicity tests and transfection experiments were then used to examine the role and the regulation mechanisms of selected miRNAs. RESULTS: We identified a robust collection of 20 miRNAs significantly deregulated in ER(+) compared to ER(−) breast cancers : 12 up-regulated and eight down-regulated miRNAs. MiR-190b retained our attention as it was the miRNA the most strongly over-expressed in ER(+) compared to ER(−) with a fold change upper to 23. It was also significantly up-regulated in ER(+)/Normal breast tissue and down-regulated in ER(−)/Normal breast tissue. Functional experiments showed that miR-190b expression is not directly regulated by estradiol and that miR-190b does not affect breast cancer cell lines proliferation. Expression level of miR-190b impacts metastasis-free and event-free survival independently of ER status. CONCLUSIONS: This study reveals miR-190b as the highest up-regulated miRNA in hormone-dependent breast cancers. Due to its specificity and high expression level, miR-190b could therefore represent a new biomarker in hormone-dependent breast cancers but its exact role carcinogenesis remains to elucidate. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-015-1505-5) contains supplementary material, which is available to authorized users.